Prospective Clinical Research of the Efficacy of Platelet-rich Plasma in the Outpatient-based Treatment of Rotator Cuff Tendinopathy - Ho-Won Lee; Kyung-Ho Choi; Jung-Youn Kim; Ik Yang; Kyu-Cheol Noh (Clinics in Shoulder and Elbow, 2019)
Background The purpose of this study is to compare the clinical outcomes of the control group and platelet-rich plasma (PRP) group among the patients who failed to respond to conservative treatment as outpatient-based therapy for rotator cuff tendinopathy, and to compare the clinical results of leukocyte-poor (LP) PRP and leukocyte-rich (LR) PRP. Methods Inclusion criteria are (1) over 18-year-old, (2) patients with rotator cuff tendinopathy, no rotator cuff tear by radiologic diagnosis (ultrasonography or magnetic resonance imaging) within the last 3 months, and (3) not effective to conservative treatment for more than 1 month. Of the final 60 subjects, 33 patients in the exercise treatment group and 27 patients in the PRP injection group (LP-PRP, 13; LR-PRP, 14) were included. Clinical evaluation was carried out by assessing the outcomes of treatment using the Numeric Rating Scale pain score, the American Shoulder and Elbow Society (ASES) score, and the Constant score at baseline and at 3 and 6 months after the procedure. Results There was a statistically significant difference in ΔASES3months (ASES3months-ASESfirst) score between the control and PRP groups (p=0.006). However, there was no statistical significance between LP-PRP and LR-PRP groups (p>0.05). Conclusions This study showed that PRP injection was more effective than exercise therapy for the first 3 months. However, there was no difference between the LP-PRP group and the LR-PRP group. Regardless of the type of PRP, clinical application of PRP injection in patients with rotator cuff tendinopathy seems to be effective in early treatment.